The Effectiveness of Health Education with Flip Chart Media on Student's Knowledge of Basic Sanitation for Islamic Boarding Schools - Dewi, Ervi Rachma; Caesar, David Laksamana (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Background: Islamic boarding school sanitation is a public health effort that focuses on monitoring the physical structure, where people use it as a shelter which affects the degree of human health. If monitoring activities are not carried out at the Islamic Boarding School, it can increase the risk or the emergence of a disease, such as diarrhea, ARI, and scabies. Based on a preliminary survey conducted at Raudlatuth Thullab Islamic Boarding School, the sanitation inspection activity obtained a score of 1,950, which means that sanitation problems are still found at the Islamic Boarding School. The standard score that meets the requirements for Islamic boarding schools is in the range of 2,130 - 3,550. The purpose of this study was to analyze the effectiveness of health education using flip chart media on increasing students' knowledge about basic sanitation at Islamic boarding schools. Methods: This research is a type of pre-experimental research with a one-group pretest-posttest design. The number of samples in this study was 32 students who lived in Raudlatuth Thullab Islamic Boarding School. Results: The results of this study indicate that Health Promotion using flip chart media is effective in increasing students' knowledge about basic sanitation at Raudlatuth Thullab Islamic Boarding School. Conclusions: Health Promotion using flip chart media has a role in increasing students' knowledge of Islamic boarding school basic sanitation, so it is hoped that proper basic sanitation can reduce the incidence of infectious diseases in Islamic boarding schools.